Geometric quadratic stochastic operator on countable infinite set - Ganikhodjaev, Nasir; Hamzah, Nur Zatul Akmar (American Institute of Physics, 2015)
In this paper we construct the family of Geometric quadratic stochastic operators defined on the countable sample space of nonnegative integers and investigate their trajectory behavior. Such operators can be reinterpreted in terms of of evolutionary operator of free population. We show that Geometric quadratic stochastic operators are regular transformations.